SOME CORRECTIONS FOR THE RESIDUAL NUCLEI FORMATION CROSS SECTIONS AT THE IRRADIATION OF TIN ISOTOPES BY THE $^{12}$C IONS AT THE ENERGY 2.2 $GeB$/NUCLEON - Balabekyan, A. R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
The presence of constant flux of particles falling on the target is presupposed while determining the yields of residual nuclei by the induced activity method. However in reality the beam of particles possesses fluctuation. In the present work these fluctuations were considered when determining the intensity of the beam of particles. In some cases the corrections of the fluctuations are of about 30%.
Keywords: induced activity method; particles possesses fluctuation; residual nuclei